A house in the sky : a memoir - Lindhout, Amanda; Corbett, Sara. (New York Scribner, 2013)
"The spectacularly dramatic memoir of a woman whose curiosity about the world led her from rural Canada to imperiled and dangerous countries on every continent, and then into fifteen months of harrowing captivity in Somalia"--
Keywords: Lindhout, Amanda; Journalists -- Canada -- Biography; Hostages -- Somalia -- Biography; Somalia -- History -- 1991-